Project GRAMS a Graphical Reconfigurable Architecture MIPS Simulator - Bautista, Patrick Ian
Studying trade-off analysis in computer architecture and higher-level computer organization can be very hard due to the small amount of detail given to it in undergraduate courses. The key concepts and processes taking place can be very difficult to understand by using pen and paper alone. A graphical simulator can be utilized to represent the concepts in a very intuitive and interactive manner thus revolutionizing and simplifying the way students and instructors learn and teach computer architecture. One of Project GRAMS' primary objectives is to provide methods to easily visualize the effects of instruction set reconfiguration in various datapath implementations. Another objective is to enable users to code and compile machines programs for testing a particular configuration's performance and flexibility. Lastly, the software will be programmed to present a contextual and graphical representation of data exchange processes during an instruction's execution. The project will be coded using JAVA and will be designed to run in various computer platforms available in the academe.